An experimental investigation of the formability of low carbon steel tailor-welded blanks of different thickness ratios. Issue 5 (February 2017) - Elshalakany, Abou; Ali, Shady; Osman, T.; Megaid, H.; Mokadem, A.
Abstract Cold-rolled low carbon steel sheets of thicknesses ranging from 0.8 to 2 mm were sheets welded together to form a single part before the formability tests. In this study, the formability of the tailor-welded blanks (TWBs) was evaluated in terms of three measures which are limited dome height (LDH), forming limit diagram (FLD), and minimum major strain. In addition to the mechanical properties, the welded specimens were analyzed experimentally under the effect of thickness ratios. The influence of welding orientation and its relation with the rolling direction on formability and mechanical properties were also studied. The mechanical properties of the welded specimens were investigated by tensile testing and micro-hardness measurements. The metallographic studies were investigated using optical microscope and scanning electron microscope (SEM). The experimental findings in this study showed that the higher the thickness ratio of the TWBs, the lower the forming limits curve level and the lower formability. The minimum major strain was clearly inversely proportional to the thickness ratio of the TWBs. On the other hand, the results of uniaxial tests clearly illustrated that there was no significant difference between the tensile strengths of the TWBs and base metal. The micro-hardness measurements indicated that the hardness in the weld bead increased by about 55 % of the base metal.